2019
DOI: 10.1016/j.erss.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility capital and flexibility justice in smart energy systems

Abstract: Flexibility has increasing value across sectors of the economy, including energy. The ability to be flexible is affected by a wide variety of sociotechnical factors and determines what we term 'flexibility capital'. Levels of flexibility capital vary in populations, both absolutely and in the extent to which they are primarily derived from technological or social means, which has implications for the (dis)comfort and (in)convenience involved in economising flexibility capital. Furthermore, we argue that freedo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…Failure to recognise differences in citizen's capacities to engage in flexibility was seen as underpinning a range of potential injustices, from the imposition of less accessible procedures for engagement with the energy system, to the exacerbation of existing patterns of inequality and marginalisation. Such concerns mirror clearly recent work by in the energy justice literature, in particular the notion of social and economic 'flexibility capital' capital proposed by Powells and Fell [9] as two axis along which energy injustices may be emerge. Our findings in this area thus suggest that not only is there a congruence between scholarly conceptualisations of energy justice and the moral frameworks through which citizens make sense of energy system governance, but that among our participants at least, ensuring equality of access to and status in more flexible energy systems and providing mitigation for those who may struggle was of particular importance in assessing the desirability of potential pathways for transitions towards energy systems flexibility.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Failure to recognise differences in citizen's capacities to engage in flexibility was seen as underpinning a range of potential injustices, from the imposition of less accessible procedures for engagement with the energy system, to the exacerbation of existing patterns of inequality and marginalisation. Such concerns mirror clearly recent work by in the energy justice literature, in particular the notion of social and economic 'flexibility capital' capital proposed by Powells and Fell [9] as two axis along which energy injustices may be emerge. Our findings in this area thus suggest that not only is there a congruence between scholarly conceptualisations of energy justice and the moral frameworks through which citizens make sense of energy system governance, but that among our participants at least, ensuring equality of access to and status in more flexible energy systems and providing mitigation for those who may struggle was of particular importance in assessing the desirability of potential pathways for transitions towards energy systems flexibility.…”
Section: Discussionsupporting
confidence: 61%
“…Turning to more contemporary debates around energy system flexibility, some interventions such as smart and demand side response technologies have been touted in straightforward liberal terms as empowering consumers [33], providing them with the tools needed to manage and optimise their energy conduct more efficiently [34]. However, should such measures fail to anticipate the needs of groups who lack the ability to engage in flexibility, they may risk exacerbating pre-existing inequalities [9]. Public perceptions research into smart energy networks have consistently found concerns that groups such as the elderly, chronically ill, disabled and low income families may have specific energy needs that are unsusceptible to time-shifting, and may lack the financial and knowledge capacities needed to engage with smart systems designed to automate such processes [35][36][37].…”
Section: Justice and Flexibility In Uk Energy Policymentioning
confidence: 99%
See 1 more Smart Citation
“…As well as addressing these limitations, future research should examine how communities with low resources and limited renewable generation capacity understand and seek to participate in P2P energy markets. Evidence suggests that the decarbonization process and P2P energy trading could place additional burdens on low-resource households and communities [10,46]. Thus, it is important to explore implications for these populations.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Nonetheless, the status of vulnerable households with lower disposal income should also be taken into account carefully, to avoid negative impacts (e.g. discomfort) on them (Powells and Fell 2019). DSR promotion strategies can also be designed based on different genders' willingness to shift different types of appliances.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%